Coronary CT angiography using iterative reconstruction vs. filtered back projection: evaluation of image quality - Arcadi, Teresa; Maffei, Erica; Mantini, Cesare; Guaricci, Andrea; La Grutta, Ludovico; Martini, Chiara; Cademartiri, Filippo (Acta Biomedica Atenei Parmensis, 2015)
Objectives: To compare image quality of iterative reconstruction algorithm(IRIS) vs. standard filtered back projection(FBP) reconstruction in CT Coronary Angiography (CTCA). Materials and methods: Thirty-four consecutive patients underwent CTCA for suspected or known CAD with Dual-Source CT (DSCT-Flash, Siemens). All datasets were reconstructed with 0.75/0.4 and 0.6/0.4 mm slice thickness/increment, using three standard FBP kernels (B26-B30-B46) and three comparable IRIS algorithms (I26-I30-I46). Vascular attenuation and noise were measured. CT vascular attenuation values [HU] were measured in: ascending aorta (Ao), right (RCA) and left (LCA) coronary artery, respectively. Signal-to-noise (SNR) and contrast-to-noise (CNR) ratio were calculated. A p-value